Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2001
DOI: 10.1145/365024.365130
|View full text |Cite
|
Sign up to set email alerts
|

Social navigation of food recipes

Abstract: The term Social Navigation captures every-day behaviour used to find information, people, and places -namely through watching, following, and talking to people. We discuss how to design information spaces to allow for social navigation. We applied our ideas in a recipe recommendation system. In a follow-up user study, subjects state that social navigation adds value to the service: it provides for social affordance, and it helps turning a space into a social place. The study also reveals some unresolved design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 16 publications
0
43
0
1
Order By: Relevance
“…Social navigation has been studied and used in a variety of collaborative domains such as helping users select news stories [19], recipes [23], and research articles [15]. A more complete review can be found in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Social navigation has been studied and used in a variety of collaborative domains such as helping users select news stories [19], recipes [23], and research articles [15]. A more complete review can be found in [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, his approach requires an extensive knowledge base and it is unclear whether elements like taste and texture can be automatically derived from a recipe text. A recipe navigation system with social recommendations is studied by Svensson et al [12]. A collaborative filtering approach is applied, based on rating for shared recipes.…”
Section: Related Workmentioning
confidence: 99%
“…A meal recommender system based on user browsing patterns is presented by Svensson et al [10]. Freyne et al investigated three recommender strategies, which break down meals into ingredients for generating recommendations [2].…”
Section: Related Workmentioning
confidence: 99%